Training and educational technology: ORGANIZATIONAL DEVELOPMENT IN THE SOUTH AFRICAN DEFENCE FORCE - Dugmore, P.B.G. (Scientia Militaria - South African Journal of Military Studies, 2012)
This article deals with an Organizational Development Programme which started in the Defence Force in October 1976. It highl ights the preparation for, and the place of Situational Leadership Seminars and Team Building sessions in this highly bureaucratic organization.